Resistance to amyloid plaque pathology in the oldest‐old: Results from the 90+ study: Dementia care research (research projects; nonpharmacological) / Behavioral interventions. (7th December 2020) - Greenia, Dana E; Yan, Rui; Paganini‐Hill, Annlia; Corrada, Maria MM; Kawas, Claudia H
Abstract: Background: Although cerebral amyloid deposition is highly associated with age, many elderly individuals show apparent 'resistance' to amyloid pathology, with little or none at autopsy. Our objective was to examine factors associated with resistance to amyloid pathology in people 90 years and older. Method: Participants were 287 deceased individuals who had agreed to brain autopsy as part of The 90+ Study, an ongoing investigation of aging and dementia. We examined demographic factors, ApoE genotype and past medical history reported by participants or, if cognitively impaired, their surrogates. Participants were evaluated every 6 months with neurological examination and neuropsychological testing. Cognitive status (normal, cognitively impaired no dementia [CIND], or dementia) was assigned postmortem during a multidisciplinary case‐conference without knowledge of pathological findings. Amyloid plaque pathology was scored according to CERAD (Consortium to Establish a Registry for Alzheimer's disease staging) and dichotomized as absent (Stage 0) or present (sparse, moderate, frequent). We used logistic regression with absence of amyloid plaques (CERAD Stage 0) as the outcome of interest. Education was dichotomized as <college degree vs. > college degree. All analyses adjusted for sex and age at death. We repeated analyses stratifying by cognitive status. Result: At death, participants' median age was 97 years (range:90‐108), 72% were women, 50% were college graduates, and 75% had amyloid plaque pathology. Among all participants, the odds for absence of amyloid plaques (resistance) was 75% greater in college graduates compared with those with less education (OR=1, 75) (Figure). When stratified by cognitive status, education was related to absence of amyloid plaques in individuals with normal cognition (OR=4.02), but not in those with cognitive impairment. ApoE genotype and medical history variables were not related to absence of amyloid plaques (Table). Conclusion: In our study of oldest‐old participants, high education (college degree or more) was associated with absence of amyloid plaque pathology in those with normal cognition. Education may contribute to amyloid resistance in late life through a variety of potential biological mechanisms related to cerebral health and neural efficiency, or through associated lifestyle, activities and other factors.